Design and optimization of hollow microneedle spacing for three materials using finite element methods - Xiaodan Zhang; Qifei Gu; Xue Sui; Jie Zhang; Jingwei Liu; Rui Zhou (Scientific Reports)
Abstract The main advantages of microneedles are precise drug delivery through human skin, minimal tissue damage and painlessness. We conducted structural analysis and skin puncture studies of hollow microneedles using ANSYS for three materials: Hafnium Dioxide (HfO2), Polyglycolic acid (PGA) and Polylactic acid (PLA). Firstly, we selected three lengths, three tip diameters and three base diameters to conduct a L9(34) orthogonal experiment. Thus, we obtained nine different single-needle structures for each material, totaling 27 models for three materials. Subsequently, we investigated the stability and puncture properties of single needles. The optimal structures of the single-needle for three materials were same. Then, we used the optimal structure of the single-needle to establish the double-needle, triple-needle and five-needle models with ten different spacings. The simulations were carried out to examine the maximum stress during puncture. Finally, we investigated the hydrodynamic properties of water and lidocaine ibuprofen [Lid][Ibp] in the lumen of the microneedle. The results indicated that the optimal spacing of multi-needles varies depending on the material. The flow velocity of the fluid in the lumen is positively correlated with the pressure. Increasing the pressure can effectively reduce the flow velocity loss of low-viscosity fluid.